2019
DOI: 10.1177/1010539519886705
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Uric Acid and Prediabetes in the Korean General Population

Abstract: The purpose of this study is to examine the relation of serum uric acid with prediabetes in Korea. We conducted a cross-sectional study in 4633 individuals aged 20 to 81 years who participated in the 2016 Korean National Health and Nutrition Examination Survey. Participants are considered to have prediabetes if they have one or more of the following: impaired fasting glucose (fasting blood glucose levels between 5.6 and 6.9 mmol/L); impaired hemoglobin A1c (hemoglobin A1c ranges of 5.7% to 6.4% [39-46 mmol/mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
(39 reference statements)
2
1
0
Order By: Relevance
“…The relationship among SUA, FPG and serum lipid are also deserve to be mentioned. In line with previous studies (31,32), increasing trend at the mean level of TG, TC, and LDL-C were observed across the glycemic statues and SUA quartiles, while HDL-C decreased. Several putative mechanisms may be proposed for the observed results.…”
Section: Discussionsupporting
confidence: 92%
“…The relationship among SUA, FPG and serum lipid are also deserve to be mentioned. In line with previous studies (31,32), increasing trend at the mean level of TG, TC, and LDL-C were observed across the glycemic statues and SUA quartiles, while HDL-C decreased. Several putative mechanisms may be proposed for the observed results.…”
Section: Discussionsupporting
confidence: 92%
“…The relationships between SUA, FPG, and serum lipid also deserve to be mentioned. Consistent with previous studies 40,41 , an increasing trend in the mean levels of TG, TC, and LDL-C was observed across the glycemic status and SUA quartiles, while a decreasing trend in HDL-C levels was seen. Several putative mechanisms could be proposed for these findings.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, the 6‐year follow‐up data of the Chinese population indicated a strong positive association between SUA and incident prediabetes in women rather than in men 25 . Furthermore, in the Korean population, the odds of having prediabetes compared with that of not having it increased by 16% in women for an increment of 1 mg/dL in SUA ( P = 0.01); however, the odds were not significant in men ( P = 0.05) 26 . The present study was conducted among a homogeneous Japanese population and confirmed the women‐specific association between SUA and prediabetes.…”
Section: Discussionmentioning
confidence: 89%